IMPLEMENTASI METODE SIMPLE ADDITIVE WEIGHTING PADA PEMILIHAN TOKO KOMPUTER ONLINE TERBAIK - Sidik, Sidik (Jurnal Pilar Nusa Mandiri, 2015)
The concept of sales, goods, and services are also experiencing rapid transformation. If a few years ago in offering products or services are still using conventional sales methods should be meeting with the seller and the buyer, but this time with the use of the Internet network sales system has been changed. Sellers can easily peddle products and services through social media and by opening their own online stores to provide easiness transaction for the buyer. Methods SAW (Simple Additive Weighting) is a weighted sum method is based on performance ratings for each alternative on all attributes. With this method, we can make choices or take a decision with less how to determine the weight values for each attribute, followed by a ranking process that will provide the best alternative from a number of alternatives. According to this method will get results or rank (rank) that will be used as a reference in determining the choice of the discussion on the research process